Cognitive Auditory Evoked Potentials (CAEP) in poor cochlear implant users - Munivrana, Boška (Array, 2012)
There are three factors that influence successful use of cochlear implants (CI): age at implantation, duration of speech and hearing rehabilitation and auditory level after implantation. Age at implantation is the basic criterion for the estimation of success of CI usage. The optimal implantation age is beween first and second year (Sharma et al., 2002 ; Archbold et al., 2008). Relatively good success may be excpected with implantation at later age, provided that the child is included in speech and hearing rehabilitation (Theoh et al., 200). However, even when these criteria are satisfied, some children do not reach the expected outcome. Hearing disorders at higher level of the auditory pahtway may be the culprit. It is known that some children with normal hearing but with special language imapirment (SLI) have difficulties in perception and discrimination of short sounds that follow each other in short time intervals (Bishop and McArthur, 2004). Some children with SLI have difficulties in the discrimination of frequency characteristics of sound. Those children have impaired time processeing of acoustic simuli (Bishop et al., 2007). Perception and discrimination of auditory and speech stimuli in children aged 8-10 years who are poor CI users (n=10) and 10 healthy age-matched controls were investigated using cognitive auditory evoked potential technique (CAEP). The measurements were performed with a 32-channel Neuroscan electroencephalographic system. Two types of stimuli were applied: Pure tones (1 kHz and 2 kHz) and double CV syllabi (ka-ka, te-te). The stimuli were presented in and odd-ball paradigm, requiring a conscious reaction of the subjects to target stimuli. Latencies and amplitudes of P1, N1, P2, N2, P3 and SW waves were analyzed, as well as the reaction time and number of responses. Statistically significant differences were found between CI users and the control group in average response time and number of responses to tone burst and double syllable. Analysis of variance of all used variables showed a statistically significant differences in all wave latencies after pure tone stimulation after target and non target stimulation ; P2 wave amplitude after non target stimulation and P3 wave amplitude after target stimulation. In addition, analysis of variance showed a statistically significant difference in all wave latencies after double syllabe non target stimulation except N1 wave latencies ; P3 wave latencies for non target stimulation and N2 wave for non target stimulation. Our study showed that unsuccessful CI users take longer time to percieve and discriminate between both tonal and speech stimuli than children with normal hearing and typical speech and language development.